KSu swine enterprise record summary - Michael R Langemeier; Robert D Goodband; Michael D Tokach (Kansas Agricultural Experiment Station Research Reports, 1992)
Approximately 35 swine operations are enrolled in the 1992 Kansas Swine Enterprise Record Program. This program evaluates physical and economic performance and is part of a cooperative record-keeping project with extension personnel and swine producers in Kansas, Nebraska, and South Dakota. Records are summarized every 6 months, and the corresponding data are pooled to form state and regional averages. This paper summarizes the data for 22 farrow-to-finish operations in Kansas that kept records during the first 6 months of 1992. Profit per cwt. of pork produced for these 22 producers averaged 1.13. Profits varied substantially between producers. Producers in the top one-third in terms of profitability had average profits of 8.25 per cwt., whereas producers in the bottom one-third had average losses of 7.02 per cwt. Critical factors separating low and high profit producers included feed costs, unpaid labor, fixed costs, and productivity.; Swine Day, Manhattan, KS, November 19, 1992
Keywords: Swine day; 1992; Kansas Agricultural Experiment Station contribution; no. 93-142-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 667; Swine; Enterprise record summary